The Influence of Employee Commitment, Leadership and Individual Characteristics on Employee Work Motivation, Leadership and Individual Characteristics on Employee Work Motivation: The Influence of Employee Commitment, Leadership and Individual Characteristics on Employee Work Motivation - Budiwati, Budiwati; Khuzaini, Khuzaini; Zainul, Zainul; M. Irpan, M. Irpan (PT. Hanken SUkses Jaya, 2024)
This research aims to analyze the influence of commitment, leadership and individual character on employee work motivation in the Provincial Women's Empowerment, Child Protection and Family Planning Service. South Kalimantan, this is indeed crucial and significant in achieving organizational goals, so as to improve the performance of employees in the SKPD environment in the South Kalimantan provincial government. This research method uses a qualitative method, using SPSS version 24, data and data sources obtained from independent variables, namely Commitment (X1), Leadership (X2) and individual characteristics (X3) and Work Motivation (Y). Data analysis techniques are carried out using Descriptive Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing, both Persial t Statistical Tests, F Stimulant Statistical Tests, Determination Coefficients and Reliability Validity Tests. The research results show that the implications of the research results show that commitment, leadership and individual characteristics can influence the motivation of employees of the Provincial Women's Empowerment, Child Protection and Family Planning Service. South Kalimantan, can increase employee motivation through organizational leaders who continue to encourage their employees by providing guidance and direction consistently and continuously.